Trends and Bottlenecks in Virtual Reality and Tactile Interaction Technologies - Meng, Jibing (Journal of Artificial Intelligence and Information, 2025)
The main form of artistic expression of virtual reality technology is not visual expression. In the course of human history development, visual art plays an extremely significant role, such as ancient mural art, Western Han shadows and modern cinema and television are all visual arts, and these are vivid reflections of economic life and scientific and technological standards during the stage of human social development, becoming the essence of human civilization development. Art comes from everyday life and is above life. It not only records all aspects of human life, but also reflects people's aspiration for a better life and their boundless vision for the future. Visual expression not only allows the plot of the story to be more vivid, but also brings people a sense of enjoyment. This article explores the trends and bottlenecks of virtual reality and tactile interaction technology.